Perirenal hematoma: a rare complication of anticoagulant therapy - Silva, Frederico (2023)
Hemorrhagic complications arising from anticoagulant use are a well-recognized concern in clinical practice. This case study presents an 84-year-old woman with multiple cardiovascular risk factors, including atrial fibrillation, who developed a perirenal hematoma after just five doses of enoxaparin, prescribed for stroke prevention. The patient exhibited altered mental status and abdominal pain, prompting imaging studies revealing the hematoma. This case highlights the importance of vigilance in patients at risk for bleeding complications, especially in the initial days of anticoagulant therapy. Diagnostic imaging, particularly CT scans or ultrasound, is crucial for early detection. Management strategies range from discontinuing anticoagulants to potential interventions like anticoagulation reversal, angiography, or surgery. The decision to resume anticoagulation presents a challenge and requires a personalized approach based on patient factors. This case underscores the need for continued vigilance, early diagnosis, and evidence-based decisions in managing patients on anticoagulants, emphasizing the necessity for further research to establish clear guidelines in such complex clinical scenarios.